The murder of Roger Ackroyd - Christie, Agatha, 1890-1976. (1983)
The death of a wealthy widow is believed to be an accident until her future husband is killed. The police bring in Hercule Poirot to help with the investigation.
Keywords: Poirot, Hercule -- (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Belgians -- England -- Fiction; Detective and mystery fiction